An experimental validation of a new shape optimization technique for piezoelectric harvesting cantilever beams - Khaled Mohamed; Hassan Elgamal; Sallam A. Kouritem (Alexandria Engineering Journal, 2021)
The piezoelectric energy harvester efficiency depends on optimizing the cantilever geometry and tuning its natural frequency with vibration source frequency. Moreover, the effect of harvester parameters on natural frequency is vital in tuning the resonance frequency. So, a COMSOL Multi-physics finite element analysis, Eigen frequency study and analytical analysis using MATLAB were constructed to calculate the resonance frequencies and to analyze the harvester parameters effect. Five harvester different shapes, namely, the T-shaped, rectangular, L-shaped, variable width, and triangular cantilevers were optimized using the genetic algorithm. The simulation of the five shapes was implemented using COMSOL. The results indicated that the T- shaped cantilever produced the largest power. Due to its high power and inclusive shape, the T-shaped cantilever with variable width was optimized using the COMSOL optimization module (BOBYQA). Linking genetic algorithm and COMSOL optimization module has highly improved the output power. The COMSOL results were validated using an experimental setup of piezoelectric cantilevers. The experimental setup was employed to calculate the voltage of the base excited harvester with very low excitation frequencies from 0.5 to 10 Hz. Also, the experimental setup investigated the effect of the tip mass, length of the cantilever, and piezoelectric material volume on the output voltage.